PENERAPAN MEDIA BENDA KONKRET PADA PEMBELAJARAN BANGUN DATAR DI KELAS 2 - Zurmida Dwi Nazulfah; Achmad Fanani; Cholifah Tur Rosidah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study's goal is to learn how to use concrete object media in class 2. This depends on educators who have not involved substantial article media in learning science. So the scientist expects to help educators in the use of substantial item media by presenting a proposal research named "Use of Substantial Article Media in Learning Level Shapes in Class 2 on the material qualities of level shapes.This research utilizes clear quantitative examination. The students in class 2 are the subject of this research's data. The information assortment methods utilized are perception, tests, and polls. The results of this study using concrete object media in learning flat shapes in class 2 show that student activities were in the good category with a score of 94.9, which indicates the validity of the data used in this study. Concerning the learning results to get a decent classification get a score of 79.7.